Genome-scale profiling of histone H3.3 replacement patterns. - Mito, Y.; Henikoff, J.G.; Henikoff, S. (Nature Genetics, 2005)
Histones of multicellular organisms are assembled into chromatin primarily during DNA replication. When chromatin assembly occurs at other times, the histone H3.3 variant replaces canonical H3. Here we introduce a new strategy for profiling epigenetic patterns on the basis of H3.3 replacement, using microarrays covering roughly one-third of the Drosophila melanogaster genome at 100-bp resolution. We identified patterns of H3.3 replacement over active genes and transposons. H3.3 replacement occurred prominently at sites of abundant RNA polymerase II and methylated H3 Lys4 throughout the genome and was enhanced on the dosage-compensated male X chromosome. Active genes were depleted of histones at promoters and were enriched in H3.3 from upstream to downstream of transcription units. We propose that deposition and inheritance of actively modified H3.3 in regulatory regions maintains transcriptionally active chromatin.